2015
DOI: 10.1103/physrevd.92.125011
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics, resurgence, and transasymptotics

Abstract: The second-order hydrodynamical description of a homogeneous conformal plasma that undergoes a boostinvariant expansion is given by a single nonlinear ordinary differential equation, whose resurgent asymptotic properties we study, developing further the recent work of Heller and Spalinski [Phys. Rev. Lett. 115, 072501 (2015)]. Resurgence clearly identifies the non-hydrodynamic modes that are exponentially suppressed at late times, analogous to the quasi-normal-modes in gravitational language, organizing these … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
113
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(120 citation statements)
references
References 43 publications
7
113
0
Order By: Relevance
“…In Minkowski space with 1 Previous studies of the Bjorken model have shown that after rewriting the hydrodynamical equations for the temperature and the only independent component of the shear viscous tensor in terms of the variable w ¼ τTðτÞ (where τ and T are the longitudinal proper time and temperature) reduce effectively to a truly 1D nonlinear differential equation [20,26,27,36,37]. The solution of this equation for a suitable initial condition determines what has been, by abuse of terminology, called the "attractor solution."…”
Section: Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…In Minkowski space with 1 Previous studies of the Bjorken model have shown that after rewriting the hydrodynamical equations for the temperature and the only independent component of the shear viscous tensor in terms of the variable w ¼ τTðτÞ (where τ and T are the longitudinal proper time and temperature) reduce effectively to a truly 1D nonlinear differential equation [20,26,27,36,37]. The solution of this equation for a suitable initial condition determines what has been, by abuse of terminology, called the "attractor solution."…”
Section: Setupmentioning
confidence: 99%
“…We take the late-time or asymptotic limit tanh 2 ρ ∼ 1 which was explained before and it poses no problem in the universality of the attractor due to the exponentially fast convergence of flow lines toward it at late times. In the case of IS and DNMR this constraint gives two different solutions so one chooses only the stable one A þ ðwÞ [25,26], which are respectively given by…”
Section: Universal Asymptotic Attractors For Different Dynamical mentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that hydrodynamic theory cannot be systematically improved by taking into account higher order-terms in the gradient series [26]. The gradient expansion generates an asymptotic series which exhibits initial signs of convergence for a few terms before eventually diverging [26,28]. The initial appearance of convergence may explain the observed remarkable phenomenological success of hydrodynamic formulations based on truncations of the gradient expansion at second or third order but, due to the ultimate divergence of the series, the theory cannot be improved beyond a certain order by keeping additional terms.…”
Section: Introductionmentioning
confidence: 99%
“…The strong coupling side of planar = 4 SU(N ) SYM can also be studied within the context of the AdS/CFT correspondence. In particular it was realised in [28] that the hydrodynamic gradient series for the strongly coupled = 4 super Yang-Mills plasma is only an asymptotic expansion leading to the works [29][30][31] dealing with resurgence and resummation issues in the fluid context of AdS 5 /CFT 4 .…”
Section: Introductionmentioning
confidence: 99%